Titanium-based mixed powder for laser cladding coating and manufacturing method
By using titanium-based mixed powder and high-pressure sintering process, the problem of agglomeration of carbide ceramic particles during laser cladding is solved, the high hardness and wear resistance of the coating are achieved, and the overall performance of the material is improved.
Patent Information
- Application Number
- CN202411703966.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-26
AI Technical Summary
During laser cladding, carbide ceramic particles are prone to agglomeration, resulting in difficulty in uniform distribution within the cladding layer, affecting the hardness and wear resistance of the coating.
Titanium-based mixed powders, including Ti powder, carbon nanotubes, carbon black, graphite, silicon carbide and fluorinated graphite, are used to form titanium carbide and silicon titanium carbide composite materials through high-pressure sintering process to promote the full bonding of materials and the uniform distribution of the hard phase.
The hardness and wear resistance of the laser cladding coating are improved, and the mechanical properties of the material are enhanced.
Smart Images

Figure CN119506658A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field related to metal coatings, and in particular to a titanium-based mixed powder for laser cladding coatings and a manufacturing method thereof. Background Art
[0002] Laser cladding uses cladding materials that have good compatibility but are mostly different from the matrix composition. Laser beam heating is used to prepare a cladding layer on the alloy surface that forms a good metallurgical bond with the alloy matrix, thereby improving the hardness, oxidation resistance, corrosion resistance, wear resistance and biological properties of the matrix surface.
[0003] Cladding materials are formed into cladding layers by laser cladding under appropriate process parameters. Cladding materials directly affect the chemical composition of the coating. Cladding materials can be divided into powder materials, wire materials, and plates in terms of shape. Powder materials interact well with lasers during use and are flexible to use. Therefore, powder materials have become the most widely used and versatile cladding materials.
[0004] Ceramic particles are the main reinforcing phase of the composite cladding layer, and play a key role in improving the hardness and wear resistance of the cladding layer. There are many types of ceramic particles, mainly oxide ceramics, carbide ceramics, nitrides and borides. Carbide ceramics can be divided into metal carbides (such as TiC) and non-metallic carbides (such as SiC); but during the cladding process, carbide ceramic particles tend to agglomerate and cannot be evenly distributed in the cladding layer, affecting the hardness and wear resistance of the cladding layer. Summary of the invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a titanium-based mixed powder for laser cladding coating. The laser cladding coating made by using the powder has high hardness and good wear resistance.
[0006] Specifically, the first aspect of the present application provides a titanium-based mixed powder for laser cladding coating, comprising the following raw materials in parts by weight: 50 parts of Ti powder, 2 to 4 parts of carbon nanotubes, 5 to 6 parts of carbon black, 1 to 3 parts of graphite, 12 to 15 parts of silicon carbide and 5 to 7 parts of graphite fluoride.
[0007] According to one technical solution of the titanium-based mixed powder technical solution of the present application, at least the following beneficial effects are achieved: The raw materials for preparing the titanium-based mixed powder in the present application include Ti powder, carbon nanotubes, carbon black, graphite, silicon carbide and graphite fluoride; wherein titanium powder is used as a titanium source to form titanium carbide and titanium silicon carbide (Ti3SiC2); during the preparation process, carbon nanotubes, carbon black, graphite and graphite fluoride react with titanium powder to form titanium carbide, and titanium powder reacts with silicon carbide to form titanium silicon carbide.
[0008] Carbon nanotubes are fibrous with a small diameter, carbon black is granular, and graphite is a soft phase with strong adhesion and a relatively large contact area. The three are used to form a three-dimensional structure of points, lines and surfaces, which has a certain supporting effect on titanium powder, can promote full contact between titanium powder and carbon materials, and thus facilitate the formation of uniform titanium carbide materials.
[0009] In the present application, graphite fluoride is also used to promote the formation of titanium carbide. During the reaction, graphite fluoride will partially decompose to produce F atoms and highly active carbon. The F atoms are highly active and will first react with Ti powder to form TiF3; TiF3 will further react with highly active carbon to form TiC and fluorine atoms, thereby promoting the formation of TiC.
[0010] The present application also controls the proportion of titanium carbide and silicon titanium carbide by controlling the weight proportions of the raw materials, thereby producing a mixed powder with excellent performance.
[0011] According to some embodiments of the present application, the particle size of the titanium powder is 20 μm to 30 μm.
[0012] According to some embodiments of the present application, the diameter of the carbon nanotube is 5nm~15nm.
[0013] According to some embodiments of the present application, the particle size of the carbon black is 40nm~50nm.
[0014] According to some embodiments of the present application, the particle size of the graphite is 40 μm to 50 μm.
[0015] According to some embodiments of the present application, the fluorine-to-carbon ratio of the fluorinated graphite is 1.1 to 1.2.
[0016] Graphite fluoride is a covalently bonded graphite intercalation compound composed of carbon and fluorine. It has a layered structure, and fluorine atoms are its intercalation substances. The molecular formula is generally (CF x ) n express; Due to the introduction of fluorine atoms, CF bonds are formed in graphite, and fluorinated graphite with a high degree of fluorination can react with titanium powder to generate TiC; the pyrolysis temperature of fluorinated graphite with a high degree of fluorination reaches the temperature at which fluorine reacts with titanium, and the CF bonds break and react with titanium to further release a large amount of heat, which promotes the reaction between carbon and titanium; fluorinated graphite with a high degree of fluorination has a high concentration of CF bonds, and after the chemical bonds break, the concentration of highly active carbon particles formed is high, which is easy to react with titanium. The interlayer spacing of fluorinated graphite with a high degree of fluorination is large, which is conducive to the penetration of titanium particles and the reaction with carbon. The influence of multiple favorable factors promotes the reaction of fluorinated graphite with a high degree of fluorination with titanium powder to produce the target product TiC.
[0017] For fluorinated graphite with a fluorine-carbon atomic ratio greater than 1.1, since the fluorine in the fluorinated graphite exists completely in the form of CF covalent bonds, and the carbon atoms (CF) exist in sp3 hybrid orbitals, the planarity of the graphite layer changes to form wrinkles, which is more conducive to the formation of titanium carbide.
[0018] According to some embodiments of the present application, the particle size of the fluorinated graphite is 5 μm to 10 μm.
[0019] According to some embodiments of the present application, the silicon carbide includes the following preparation raw materials in parts by weight: 1 part of silica sol and 3 to 7 parts of graphite powder.
[0020] The present application adopts the direction of silica sol and graphite powder to form silicon carbide; utilizes the reaction of silica sol and graphite powder to form small-sized silicon carbide material; is conducive to the full contact between silicon carbide material and titanium powder, thereby promoting titanium silicon carbon material.
[0021] According to some embodiments of the present application, the particle size of the graphite powder is 100 μm to 200 μm.
[0022] The second aspect of the present application provides a method for preparing the titanium-based mixed powder for laser cladding coating, comprising the following steps: Mixing the prepared raw materials, pressing them into shape, and sintering them under high pressure; The pressure of the high pressure sintering is 20MPa~50MPa; The high pressure sintering temperature is 1000°C to 1600°C.
[0023] According to one of the technical solutions of the preparation method of the present application, at least the following beneficial effects are achieved: The present invention is sintered under high pressure and high temperature, so that the raw materials are fully combined with each other, so that the final material has good toughness, thereby enhancing the mechanical properties of the material.
[0024] According to some embodiments of the present application, the mixing is ball milling mixing.
[0025] According to some embodiments of the present application, the mixed medium is ethanol.
[0026] According to some embodiments of the present application, the rotation speed of the ball milling mixing is 100r / min~200r / min.
[0027] According to some embodiments of the present application, the high pressure sintering includes a first stage sintering, a second stage sintering and a third stage sintering.
[0028] According to some embodiments of the present application, the temperature of the first sintering stage is 1000°C~1100°C.
[0029] According to some embodiments of the present application, the time of the first sintering stage is 0.5h~1.5h.
[0030] According to some embodiments of the present application, the pressure of the first sintering stage is 20 MPa~30 MPa.
[0031] According to some embodiments of the present application, the temperature of the second sintering stage is 1200°C~1400°C.
[0032] According to some embodiments of the present application, the pressure of the second sintering stage is 40 MPa~50 MPa.
[0033] According to some embodiments of the present application, the second sintering time is 1.5h~2.5h.
[0034] According to some embodiments of the present application, the temperature of the third sintering stage is 1450°C~1600°C.
[0035] According to some embodiments of the present application, the pressure of the third sintering stage is 35MPa~40MPa.
[0036] According to some embodiments of the present application, the third sintering time is 0.3h~0.7h.
[0037] In the present application, the pressure and time of the first sintering stage, the second sintering stage and the third sintering stage are controlled, so as to control the degree and content of the combination of titanium carbide and titanium silicon carbon finally formed. In the first and second sintering processes, the titanium silicon carbon phase is preferentially formed, while in the third sintering process, silicon is easily evaporated and lost; under high pressure, the evaporation and escape of internal silicon is blocked, so as to achieve the control of the final titanium carbide content and titanium silicon carbon content, thereby achieving the control of the final material properties.
[0038] Among them, the hardness of titanium carbide is higher than that of titanium silicon carbide, but its machinability is poor. By regulating the content of silicon carbide and silicon titanium carbide, it is beneficial to control the hardness of the material and improve its processing performance, thereby producing a titanium-based mixed powder with excellent performance.
[0039] According to some embodiments of the present application, the first stage is further subjected to heat treatment before sintering.
[0040] According to some embodiments of the present application, the temperature of the heat treatment is 400°C to 500°C.
[0041] According to some embodiments of the present application, the heat treatment time is 2h~3h.
[0042] According to some embodiments of the present application, the method for preparing the silica sol comprises the following steps: Tetraethyl orthosilicate, ethanol, water and hydrochloric acid are mixed and reacted; The mass fraction of the hydrochloric acid is 30% to 37%.
[0043] According to some embodiments of the present application, the molar ratio of tetraethyl orthosilicate to ethanol is 1:5~7.
[0044] According to some embodiments of the present application, the molar ratio of tetraethyl orthosilicate to water is 1:5~7.
[0045] According to some embodiments of the present application, the molar ratio of the tetraethyl orthosilicate to the hydrogen chloride in the hydrochloric acid is 1:0.1~0.3.
[0046] According to some embodiments of the present application, the pressing pressure is 5 MPa~10 MPa.
[0047] According to some embodiments of the present application, the pressing time is 5s~30s.
[0048] The present application adopts a sol-gel carbon thermal reduction reaction method to prepare silicon carbide material, and then mixes the silicon carbide material, carbon nanotubes, carbon black, graphite and fluorinated graphite with titanium powder and performs high-pressure and high-temperature sintering to form a titanium carbide and silicon titanium carbide composite material. The titanium carbide and silicon titanium carbide are interspersed with each other and evenly distributed in the system, thereby producing a titanium-based mixed powder with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0050] Figure 1 This is a SEM image of the laser cladding coating made using the titanium-based mixed powder in Example 1 of the present application.
[0051] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0053] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.
[0054] Fluorinated graphite, specification: DBSF2050; average particle size: 5μm~10μm; fluorine-carbon ratio: 1.15.
[0055] Silicon carbide, the preparation method of silicon carbide in this application, consists of the following steps: S1. Mix the wastewater ethanol and ethyl orthosilicate and stir evenly, then add water and a hydrochloric acid solution with a mass concentration of 37% and stir evenly (stirring and reacting at 25°C for 30 minutes) to obtain a silica sol; The molar ratio of hydrogen chloride in anhydrous ethanol, ethyl orthosilicate, water and hydrochloric acid solution is 3:0.6:3:0.1; S2, adding graphite powder (average particle size of 150 μm, mass ratio of graphite powder to silica sol of 1:5) to the silica sol obtained in step S1, stirring for 20 min, and drying at 100° C. for 12 h to obtain graphite powder coated with silica sol; S3. Reduce the graphite powder coated with silica sol obtained in step S2 at 1350° C. for 2 h (the atmosphere is argon and the heating rate is 5° C. / min) to obtain silicon carbide.
[0056] Example 1 This embodiment is a mixed powder for laser coating, which is composed of the following raw materials in parts by weight: 50 parts of Ti powder, 3.4 parts of carbon nanotubes, 5.4 parts of carbon black, 2.4 parts of graphite, 13.8 parts of silicon carbide and 6.4 parts of graphite fluoride.
[0057] The particle size (D50) of titanium powder is 25 μm; the average diameter of carbon nanotubes is 10 nm; the particle size (D50) of carbon black is 45 nm; and the particle size (D50) of graphite is 45 μm.
[0058] The method for preparing the mixed powder for laser coating in this embodiment consists of the following steps: S1. Mix the prepared raw materials (titanium powder mass is 50g, and other materials are matched according to the proportion) and then ball mill; Ball milling parameters are as follows: The medium is anhydrous ethanol, zirconium oxide balls are used as grinding balls, the speed of ball milling is 180r / min, and the ball milling time is 15h; The diameter of the zirconia ball is φ5 mm, and the mass ratio of the zirconia ball, the preparation raw material and anhydrous ethanol is 2:1:2.
[0059] After ball milling, the mixture was dried at 60°C for 20 h, fully ground and pulverized, and then passed through a 200-mesh sieve to obtain a mixed powder.
[0060] S2. The mixed powder obtained in step S1 is placed into a mold and pressed at a pressure of 10 MPa for 10 seconds to form a mold.
[0061] S3, placing the powder after pressing in step S2 in a hot pressing sintering furnace, heating to 450°C under argon protection and keeping the temperature for 2 hours (heating rate is 10°C / min); after the insulation, high pressure sintering (heating rate is 5°C / min); High pressure sintering includes first stage sintering, second stage sintering and third stage sintering.
[0062] The temperature of the first sintering stage is 1050°C, the time of the first sintering stage is 1h, and the pressure of the first sintering stage is 25MPa.
[0063] The temperature was increased during the first and second sintering stages at a rate of 5°C / min; The temperature of the second sintering stage is 1300°C, the pressure of the second sintering stage is 45MPa, and the time of the second sintering stage is 2h.
[0064] The temperature was increased during the second and third sintering stages at a rate of 5°C / min; The temperature of the third sintering stage is 1500°C, the pressure of the third sintering stage is 40MPa, and the time of the third sintering stage is 0.5h.
[0065] After the third stage of sintering is completed, the furnace is cooled.
[0066] Example 2 This embodiment is a mixed powder for laser coating, which is composed of the following raw materials in parts by weight: 50 parts of Ti powder, 2 parts of carbon nanotubes, 6 parts of carbon black, 1 part of graphite, 15 parts of silicon carbide and 5 parts of graphite fluoride.
[0067] The particle size (D50) of titanium powder is 25 μm; the average diameter of carbon nanotubes is 10 nm; the particle size (D50) of carbon black is 45 nm; and the particle size (D50) of graphite is 45 μm.
[0068] The method for preparing the mixed powder for laser coating in this embodiment consists of the following steps: S1. Mix the prepared raw materials (titanium powder mass is 50g, and other materials are matched according to the proportion) and then ball mill; Ball milling parameters are as follows: The medium is anhydrous ethanol, zirconium oxide balls are used as grinding balls, the speed of ball milling is 180r / min, and the ball milling time is 15h; The diameter of the zirconia ball is φ5 mm, and the mass ratio of the zirconia ball, the preparation raw material and anhydrous ethanol is 2:1:2.
[0069] After ball milling, the mixture was dried at 60°C for 20 h, fully ground and pulverized, and then passed through a 200-mesh sieve to obtain a mixed powder.
[0070] S2. The mixed powder obtained in step S1 is placed into a mold and pressed at a pressure of 10 MPa for 10 seconds to form a mold.
[0071] S3, placing the powder after pressing in step S2 in a hot pressing sintering furnace, heating to 450°C under argon protection and keeping the temperature for 2 hours (heating rate is 10°C / min); after the insulation, high pressure sintering (heating rate is 5°C / min); High pressure sintering includes first stage sintering, second stage sintering and third stage sintering.
[0072] The temperature of the first sintering stage is 1000°C, the time of the first sintering stage is 1h, and the pressure of the first sintering stage is 20MPa.
[0073] The temperature was increased during the first and second sintering stages at a rate of 5°C / min; The temperature of the second sintering stage is 1400°C, the pressure of the second sintering stage is 50MPa, and the time of the second sintering stage is 1.5h.
[0074] The temperature was increased during the second and third sintering stages at a rate of 5°C / min; The temperature of the third sintering stage is 1450°C, the pressure of the third sintering stage is 35MPa, and the time of the third sintering stage is 0.3h.
[0075] After the third stage of sintering is completed, the furnace is cooled.
[0076] Example 3 This embodiment is a mixed powder for laser coating, which is composed of the following raw materials in parts by weight: 50 parts of Ti powder, 4 parts of carbon nanotubes, 5 parts of carbon black, 3 parts of graphite, 12 parts of silicon carbide and 7 parts of graphite fluoride.
[0077] The particle size (D50) of titanium powder is 25 μm; the average diameter of carbon nanotubes is 10 nm; the particle size (D50) of carbon black is 45 nm; and the particle size (D50) of graphite is 45 μm.
[0078] The method for preparing the mixed powder for laser coating in this embodiment consists of the following steps: S1. Mix the prepared raw materials (titanium powder mass is 50g, and other materials are matched according to the proportion) and then ball mill; Ball milling parameters are as follows: The medium is anhydrous ethanol, zirconium oxide balls are used as grinding balls, the speed of ball milling is 180r / min, and the ball milling time is 15h; The diameter of the zirconia ball is φ5 mm, and the mass ratio of the zirconia ball, the preparation raw material and anhydrous ethanol is 2:1:2.
[0079] After ball milling, the mixture was dried at 60°C for 20 h, fully ground and pulverized, and then passed through a 200-mesh sieve to obtain a mixed powder.
[0080] S2. The mixed powder obtained in step S1 is placed into a mold and pressed at a pressure of 10 MPa for 10 seconds to form a mold.
[0081] S3, placing the powder after pressing in step S2 in a hot pressing sintering furnace, heating to 450°C under argon protection and keeping the temperature for 2 hours (heating rate is 10°C / min); after the insulation, high pressure sintering (heating rate is 5°C / min); High pressure sintering includes first stage sintering, second stage sintering and third stage sintering.
[0082] The temperature of the first sintering stage is 1100°C, the time of the first sintering stage is 0.5h, and the pressure of the first sintering stage is 30MPa.
[0083] The temperature was increased during the first and second sintering stages at a rate of 5°C / min; The temperature of the second sintering stage is 1200°C, the pressure of the second sintering stage is 40MPa, and the time of the second sintering stage is 2.5h.
[0084] The temperature was increased during the second and third sintering stages at a rate of 5°C / min; The temperature of the third sintering stage is 1600°C, the pressure of the third sintering stage is 40MPa, and the time of the third sintering stage is 0.3h.
[0085] After the third stage of sintering is completed, the furnace is cooled.
[0086] Example 4 This embodiment is a mixed powder for laser coating, which is different from the embodiment 1 in that: In the preparation method of this embodiment, no heat treatment is performed in step S3.
[0087] That is, the temperature is directly raised to the first stage sintering temperature under argon protection.
[0088] The first stage of heating is carried out at a rate of 10°C / min, and the temperature is raised to 450°C; then the second stage of heating is carried out at a rate of 5°C / min.
[0089] Example 5 This embodiment is a mixed powder for laser coating, which is different from the embodiment 1 in that: In the preparation method of this embodiment, the high pressure sintering in step S3 is a one-stage sintering.
[0090] The sintering temperature is 1500°C, the sintering pressure is 40MPa, and the sintering time is 4h.
[0091] After the third stage of sintering is completed, the furnace is cooled.
[0092] Comparative Example 1 This comparative example is a mixed powder for laser coating, which differs from Example 5 in that: The mixed powder in this comparative example is composed of the following raw materials in parts by weight: 50 parts of Ti powder, 10 parts of carbon nanotubes, 5.4 parts of carbon black, 2.4 parts of graphite and 6.4 parts of graphite fluoride.
[0093] The particle size (D50) of titanium powder is 25 μm; the average diameter of carbon nanotubes is 10 nm; the particle size (D50) of carbon black is 45 nm; and the particle size (D50) of graphite is 45 μm.
[0094] Comparative Example 2 This comparative example is a mixed powder for laser coating, which differs from Example 5 in that: The mixed powder in this comparative example is composed of the following raw materials in parts by weight: 50 parts of Ti powder, 8.4 parts of carbon black, 2.8 parts of graphite, 13.8 parts of silicon carbide and 6.4 parts of graphite fluoride.
[0095] The particle size (D50) of titanium powder is 25 μm; the average diameter of carbon nanotubes is 10 nm; the particle size (D50) of carbon black is 45 nm; and the particle size (D50) of graphite is 45 μm.
[0096] Comparative Example 3 This comparative example is a mixed powder for laser coating, which differs from Example 5 in that: The mixed powder in this comparative example is composed of the following raw materials in parts by weight: 50 parts of Ti powder, 6.2 parts of carbon nanotubes, 5 parts of graphite, 13.8 parts of silicon carbide and 6.4 parts of graphite fluoride.
[0097] The particle size (D50) of titanium powder is 25 μm; the average diameter of carbon nanotubes is 10 nm; and the particle size (D50) of graphite is 45 μm.
[0098] Comparative Example 4 This comparative example is a mixed powder for laser coating, which differs from Example 5 in that: The mixed powder in this comparative example is composed of the following raw materials in parts by weight: 50 parts of Ti powder, 3.4 parts of carbon nanotubes, 5.4 parts of carbon black, 5.6 parts of graphite, and 13.8 parts of silicon carbide.
[0099] The particle size (D50) of titanium powder is 25 μm; the average diameter of carbon nanotubes is 10 nm; the particle size (D50) of carbon black is 45 nm; and the particle size (D50) of graphite is 45 μm.
[0100] Comparative Example 5 This comparative example is a mixed powder for laser coating, which differs from Example 5 in that: The mixed powder in this comparative example is composed of the following raw materials in parts by weight: 50 parts of Ti powder, 16.6 parts of graphite and 13.8 parts of silicon carbide.
[0101] The particle size (D50) of titanium powder is 25 μm; the particle size (D50) of graphite is 45 μm.
[0102] Application Examples The mass ratio of the titanium-based mixed powder prepared in the examples and comparative examples of the present application to the cobalt powder (D50 is 100 μm) is 1:19.
[0103] S1, putting the above raw materials into a planetary ball mill and milling for 2 h to obtain an alloy powder mixture and drying it in a vacuum drying oven at 100° C. for 2 h; Ball milling parameters are as follows: Zirconia balls were used as grinding balls, the speed of ball milling was 180r / min, and the ball milling time was 15h. S2, grinding the TC4 alloy substrate using 400 mesh, 600 mesh, 800 mesh, 1200 mesh and 2000 mesh sandpaper in sequence; S3, using LDM-8060 powder feeding laser to scan the surface of TC4 alloy substrate by synchronous powder feeding method, and forming a composite coating on the surface of TC4 alloy substrate; Among them, the output power is 1.7kW, the spot diameter is 3mm, the scanning speed is 12mm / s, the powder feeding rate is 12g / min, the defocus is -1mm, and the overlap rate is 50%.
[0104] The performance of the composite coatings corresponding to the examples of the present application and the comparative examples was tested, and the test results are shown in Table 1.
[0105] Table 1 .
[0106] The difference between Example 4 and Example 1 is that without heat treatment, the promoting effect of graphite fluoride becomes worse, resulting in a decrease in TiC content and a lower hard phase content, resulting in a lower average microhardness.
[0107] The difference between Example 5 and Example 1 is that sintering at a single temperature results in a greater degree of desiliconization, a decrease in the silicon-titanium carbide content, greater processing difficulty, and poor uniformity of hard phase distribution, resulting in a lower average microhardness.
[0108] The difference between Comparative Example 1 and Example 5 is that without adding silicon carbide, silicon titanium carbide cannot be formed, and pure titanium carbide is difficult to process, resulting in poor uniformity of hard phase distribution and lower average microhardness.
[0109] The difference between Comparative Example 2 and Example 5 is that carbon nanotubes are not added, and graphite and carbon black are used instead of carbon nanotubes, which results in the inability to form a three-dimensional structure of points, lines and surfaces, which is not conducive to the formation of a uniform titanium carbide material; resulting in a deterioration in the uniformity of the hard phase distribution, resulting in a lower average microhardness.
[0110] The difference between Comparative Example 3 and Example 5 is that carbon black is not added, and graphite and carbon nanotubes are used instead of carbon black, which results in the inability to form a three-dimensional structure of points, lines and surfaces, which is not conducive to the formation of a uniform titanium carbide material; resulting in a deterioration in the uniformity of the hard phase distribution, resulting in a lower average microhardness.
[0111] The difference between Comparative Example 4 and Example 5 is that no fluorinated graphite is added, and graphite is used instead of fluorinated graphite, resulting in a decrease in the TiC content and a lower hard phase content, resulting in a lower average microhardness.
[0112] The difference between Comparative Example 5 and Example 5 is that carbon black, graphite fluoride and carbon nanotubes are not added, and graphite is partially replaced, resulting in the inability to form a three-dimensional structure of points, lines and surfaces, which is not conducive to the formation of uniform titanium carbide material and cannot promote the formation of TiC; resulting in a lower content of the hard phase and worse distribution uniformity, resulting in a lower average microhardness.
[0113] The reasons for the improvement of hardness in the implementation mode of the present application are as follows: first, dispersion strengthening: the strong convection generated in the molten pool makes the hard phase (TiC) in the composite coating evenly distributed in the cladding layer; second, the excellent properties of the composite alloy powder system can improve the mechanical properties of the composite coating.
[0114] The mixed powder used for laser coating in this application uses Co-Ti3SiC2-TiC alloy powder as raw material to prepare a composite coating on the surface of a TC4 alloy substrate, wherein Co is a toughening phase, Ti3SiC2 is a reinforcing phase, and TiC is a strengthening phase, and the three have a good synergistic effect on improving the performance of the composite coating. Compared with the TC4 alloy substrate, the average hardness of the composite coating is greatly improved, and the surface wear resistance of the TC4 alloy substrate is greatly improved.
[0115] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A titanium-based mixed powder for laser cladding coating, characterized in that: The preparation comprises the following raw materials in parts by weight: 50 parts of Ti powder, 2 to 4 parts of carbon nanotubes, 5 to 6 parts of carbon black, 1 to 3 parts of graphite, 12 to 15 parts of silicon carbide and 5 to 7 parts of graphite fluoride.
2. The titanium-based mixed powder for laser cladding coating according to claim 1, characterized in that: The particle size of the titanium powder is 20 μm to 30 μm; The diameter of the carbon nanotube is 5nm~15nm; The particle size of the carbon black is 40nm~50nm; The particle size of the graphite is 40 μm to 50 μm.
3. The titanium-based mixed powder for laser cladding coating according to claim 1, characterized in that: The fluorine-to-carbon ratio of the fluorinated graphite is 1.1 to 1.2; The particle size of the fluorinated graphite is 5 μm to 10 μm.
4. The titanium-based mixed powder for laser cladding coating according to claim 1, characterized in that: The silicon carbide comprises the following raw materials in parts by weight: 1 part of silica sol and 3 to 7 parts of graphite powder; The particle size of the graphite powder is 100 μm to 200 μm.
5. A method for manufacturing a titanium-based mixed powder for laser cladding coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing the prepared raw materials, pressing them into shape, and sintering them under high pressure; The pressure of the high pressure sintering is 20MPa~50MPa; The high pressure sintering temperature is 1000°C to 1600°C.
6. The manufacturing method according to claim 5, characterized in that: The mixing is ball milling mixing, and the mixing medium is ethanol; The rotation speed of the ball milling mixing is 100r / min~200r / min.
7. The manufacturing method according to claim 5, characterized in that: The high pressure sintering includes a first stage sintering, a second stage sintering and a third stage sintering; The temperature of the first sintering stage is 1000°C to 1100°C, and the time of the first sintering stage is 0.5h to 1.5h; The temperature of the second sintering stage is 1200°C to 1400°C, and the time of the second sintering stage is 1.5h to 2.5h; The temperature of the third stage sintering is 1450° C. to 1600° C., and the time of the third stage sintering is 0.3 h to 0.7 h.
8. The manufacturing method according to claim 5, characterized in that: The preparation method of the silica sol comprises the following steps: Tetraethyl orthosilicate, ethanol, water and hydrochloric acid are mixed and reacted; The mass fraction of the hydrochloric acid is 30% to 37%.
9. The manufacturing method according to claim 8, characterized in that: The molar ratio of tetraethyl orthosilicate to ethanol is 1:5-7; The molar ratio of tetraethyl orthosilicate to water is 1:5-7; The molar ratio of the tetraethyl orthosilicate to the hydrogen chloride in the hydrochloric acid is 1:0.1-0.
3.
10. The manufacturing method according to claim 5, characterized in that: The pressure of the pressing molding is 5MPa~10MPa.
Citation Information
Patent Citations
Carbon bearing or shaft sleeve for electronic water pump of electric automobile
CN116789452A
Medium-strength easy-to-form high-temperature corrosion-resistant weldable titanium alloy for crane exhaust system and preparation method
CN118389903A
Method for improving anti-corrosion, anti-scale, wear-resistant and temperature-resistant performance of oil pipe and pipe fitting
CN118497745A
Antiadhesive high temperature layers
CN1806020A
LUBRICANT COMPOSITION AND METHOD OF ITS PREPARATION
RU2014104202A